The use of contextual learning to promote scientific literacy in science classroom: from the aspects of higher order thinking skills - Abd. Raub, Latifah (2015)
Most studies found that Malaysian’s students have problems in scientific literacy as student’s ability to utilize science concepts, making conclusions and interpretation skills of scientific investigation in science classroom are still at a low level. Scientific literacy as a basic to foster complex thinking whereby formed based on the emphasis of higher order thinking skills such as problem-solving, decision making and science process. These skills encouraged students to develop concepts from variety topics and contexts of science and build a concrete relationship between the contents with their everyday context and situation. Meaningful learning is important for students to promote scientific literacy in science classroom. Thus, context based learning is said to be very relevant in learning and teaching process to develop scientific literacy among students. Context based learning emphasizes student-centered learning which underlined "need-to-know" basic to attract students to relate the concept learned with real-life context. However, only handful of studies is conducted probing into the need of context based learning approach to cultivate scientific literacy in science classroom. This study was conducted for investigate the effectiveness of contextual learning in improving scientific literacy skills from the aspects of student’s higher-order thinking skills.